Análisis Epistemológico del Modelo de Aprendizaje Acumulativo de Robert Gagne - Meza, Anibal (1993)
The authors review fundamental aspects of Robert Gagné's Leaming Theory, highlighting its philosophical (positivism and pragmatism) and scientific bases (behaviorism and information processing). Using an epistemological framework, these aspects are assessed in terrns of its theoretical and topical validity, as well as its technical efficiency. It is concluded that Gagné's Theory is eclectic and that its scientific contribution is taxonomic. It represents a theoretical model rather than a theory.